An improved Ras sensor for highly sensitive and quantitative FRET-FLIM imaging. - Ana F Oliveira (PLoS ONE, 2013)
Ras is a signaling protein involved in a variety of cellular processes. Hence, studying Ras signaling with high spatiotemporal resolution is crucial to understanding the roles of Ras in many important cellular functions. Previously, fluorescence lifetime imaging (FLIM) of fluorescent resonance energy transfer (FRET)-based Ras activity sensors, FRas and FRas-F, have been demonstrated to be useful for measuring the spatiotemporal dynamics of Ras signaling in subcellular micro-compartments. However the predominantly nuclear localization of the sensors' acceptor has limited its sensitivity. Here, we have overcome this limitation and developed two variants of the existing FRas sensor with different affinities: FRas2-F (K(d)∼1.7 µM) and FRas2-M (K(d)∼0.5 µM). We demonstrate that, under 2-photon fluorescence lifetime imaging microscopy, FRas2 sensors provide higher sensitivity compared to previous sensors in 293T cells and neurons.